Seasonal patterns of carbon dioxide, water and energy fluxes over the Caatinga and grassland in the semi-arid region of Brazil. (December 2017) - Silva, Paulo Ferreira da; Lima, José Romualdo de Sousa; Antonino, Antonio Celso Dantas; Souza, Rodolfo; Souza, Eduardo Soares de; Silva, José Raliuson Inácio; Alves, Edevaldo Miguel
Abstract: The Caatinga is a typical seasonally dry forest with a fine-tuned adaptation to the climatic conditions of the Brazilian semi-arid region and has been frequently replaced by grassland. As the effects of this replacement on CO2, water and energy fluxes are still unknown, simultaneous measurements of such fluxes are essential to understand the possible feedback cycles associated with the seasonal functioning of these ecosystems, and assessing the consequences of global changes. The aim of this study was to measure the CO2, water and energy fluxes in the Caatinga and grassland in the semi-arid region of Brazil. The measurements were made using the eddy covariance method in Pernambuco State, Brazil. The soil storage water (SSW) and normalized difference vegetation index (NDVI) were also determined. The sensible heat flux (H) was the main consumer of the available energy and was higher in the grassland. Based on an analysis of the decoupling factor, in the dry season evapotranspiration (ET) was controlled by vegetation, and it was controlled by atmospheric conditions in the wet season. ET over the Caatinga (1.4 mm d −1 ) was higher than over the grassland (0.8 mm d −1 ). The Caatinga and grassland acted as atmospheric carbon sources during drier periods with lower NDVI, and as carbon sinks during wetter periods with higher NDVI. During the dry season, the Caatinga stored more carbon than the grassland, while the inverse occurred in the wet season. Thus, land use change from Caatinga to grassland will tend to increase H and to decrease ET, but the CO2 fluxes will be similar. Highlights: First report of simultaneous CO2 fluxes in Caatinga and grassland in Brazil. There is significant reduction in CO2 uptake during periods of low soil water. The Caatinga was more efficient in carbon uptake during the dry season. The land use change from Caatinga to grassland will tend to increase H and to decrease ET.